Management and Outcome of Patients With Langerhans Cell Histiocytosis and Single‐Bone CNS‐Risk Lesions: A Multi‐Institutional Retrospective Study. Issue 12 (14th July 2015) - Chellapandian, Deepak; Shaikh, Furqan; van den Bos, Cor; Somers, Gino R.; Astigarraga, Itziar; Jubran, Rima; Degar, Barbara; Carret, Anne‐Sophie; Mandel, Karen; Belletrutti, Mark; Dix, David; Visser, Johannes; et al.
<x xml:space="preserve">Abstract</x> Background Children with Langerhans cell histiocytosis (LCH) and single‐bone CNS‐risk lesions have been reported to be at increased risk of diabetes insipidus (DI), central nervous system neurodegeneration (CNS‐ND), and recurrence of disease. However, it is unknown whether the addition of chemotherapy or radiotherapy changes outcomes in these patients. Methods Ten pediatric institutions across North America and Europe contributed data of their patients with LCH and single‐bone CNS‐risk lesions. Clinical information on age, sex, specific craniofacial site involvement, and intracranial extension at diagnosis, therapy, and disease course was collected for all eligible patients. Results The final analysis included 93 eligible children who were either treated with systemic therapy (chemotherapy, chemo‐radiotherapy, or radiotherapy) or local therapy (biopsy, curettage, and/or intralesional steroids). Fifty‐nine patients had systemic and 34 had local therapy. The 5‐year event‐free survival (EFS) and overall survival (OS) were 80 ± 5% and 98 ± 2% in the systemic therapy group versus 85 ± 6% and 95 ± 5% in the local therapy group. There was no statistically significant difference between either group with regard to EFS (P = 0.26) and OS (P = 0.78). On multivariable analysis, there was no significant difference among the two treatment groups after adjusting for site and intracranial soft tissue extension, nor any trend favoring systemic therapy (HR = 2.26, 95% CI = 0.77–6.70; P = 0.14). Conclusion Systemic therapy may not reduce the risk of recurrence or late sequelae in children with LCH and single‐bone CNS‐risk lesions as compared to local treatment. Pediatr Blood Cancer © 2015 Wiley Periodicals, Inc.